2022
DOI: 10.1097/coc.0000000000000950
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Analysis of Cervical Cancer Immunotherapy

Abstract: Cervical cancer is one of the most common gynecologically malignancies worldwide. Although vaccine and cervical cancer screening including human papillomavirus testing, cytology testing, and colposcopy have developed rapidly in recent years, effectively reducing cervical cancer mortality, cervical cancer remains a malignancy with higher female fatality rates worldwide and has a high risk for socioeconomically disadvantaged groups. The combination of platinumpaclitaxel and chemotherapy, possibly with the additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Inhibitors of CTLA‐4, such as ipilimumab and tremelimumab, have been extensively investigation in clinical trials, and completed phase I/II trials have shown potent immune activation in metastatic/recurrent cervical cancer. Additionally, other immune checkpoints, including OX40, GITR, TLR3, TIGIT, LAG3, TIM3, CD39, and A2AR, 326 , 327 as well as relevant agonist and antagonist antibodies, have been investigated in cervical cancer. However, none of them have been approved for use in the context of cervical cancer.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Inhibitors of CTLA‐4, such as ipilimumab and tremelimumab, have been extensively investigation in clinical trials, and completed phase I/II trials have shown potent immune activation in metastatic/recurrent cervical cancer. Additionally, other immune checkpoints, including OX40, GITR, TLR3, TIGIT, LAG3, TIM3, CD39, and A2AR, 326 , 327 as well as relevant agonist and antagonist antibodies, have been investigated in cervical cancer. However, none of them have been approved for use in the context of cervical cancer.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Cervical cancer, a gynecological malignancy, presents a high mortality rate globally and carries a poor prognosis in advanced stages. Each year, there are nearly 570,000 new cases of cervical cancer, resulting in over 300,000 female deaths [1]. Over the past decade, the introduction of novel therapies, such as anti-angiogenic therapy, immunotherapy, and targeted drugs, has contributed to improved diagnosis and treatment outcomes for cervical cancer [2].…”
mentioning
confidence: 99%